The New House - Hunt, Roderick; Roderick Hunt, 1986; Alex Brychta, 1986 (China Oxford University Press, 2017)
The Robinson family moves to a new house. The children, Biff, Chip, and Kipper, help pack and unpack. They explore the new house and meet new neighbors. It$1 (Bs a story about changes, feelings around moving, and making new friends.s
H3
Beginning to decode simple words using phonics. Needs picture support to aid comprehension. Recognizes common high-frequency and sight words (e.g.the, went, to, a). Can relate to feelings of change, new experiences, and family transitions. Developing empathy and understanding routines. Build vocabulary around home, family, and moving. Understand sequencing of events (beginning, middle, end). Engage in discussions about characters$1 (Bfeelings. Practice retelling and predicting.s
Keywords: Supplementary reading material